Phase 1 study of MRX34, a liposomal miR-34a mimic, in patients with advanced solid tumours - Hong, David S.; Kang, Yoon-Koo; Borad, Mitesh; Sachdev, Jasgit; Ejadi, Samuel; Lim, Ho Yeong; Brenner, Andrew J.; Park, Keunchil; Lee, Jae-Lyun; Kim, Tae-You; Shin, Sangjoon; Becerra, Carlos R.; et al. (British journal of cancer, 2020)
Background In this first-in-human, Phase 1 study of a microRNA-based cancer therapy, the recommended Phase 2 dose (RP2D) of MRX34, a liposomal mimic of microRNA-34a (miR-34a), was determined and evaluated in patients with advanced solid tumours. Methods Adults with various solid tumours refractory to standard treatments were enrolled in 3 + 3 dose-escalation cohorts and, following RP2D determination, expansion cohorts. MRX34, with oral dexamethasone premedication, was given intravenously daily for 5 days in 3-week cycles. Results Common all-cause adverse events observed in 85 patients enrolled included fever (% all grade/G3: 72/4), chills (53/14), fatigue (51/9), back/neck pain (36/5), nausea (36/1) and dyspnoea (25/4). The RP2D was 70 mg/m 2 for hepatocellular carcinoma (HCC) and 93 mg/m 2 for non-HCC cancers. Pharmacodynamic results showed delivery of miR-34a to tumours, and dose-dependent modulation of target gene expression in white blood cells. Three patients had PRs and 16 had SD lasting ≥4 cycles (median, 19 weeks, range, 11–55). Conclusion MRX34 treatment with dexamethasone premedication demonstrated a manageable toxicity profile in most patients and some clinical activity. Although the trial was closed early due to serious immune-mediated AEs that resulted in four patient deaths, dose-dependent modulation of relevant target genes provides proof-of-concept for miRNA-based cancer therapy. Clinical trial registration NCT01829971.